Software simulation and experimental characterisation of a rotationally asymmetrical concentrator under direct and diffuse solar radiation. (15th August 2016) - Freier, Daria; Muhammad-Sukki, Firdaus; Abu-Bakar, Siti Hawa; Ramirez-Iniguez, Roberto; Abubakar Mas'ud, Abdullahi; Albarracín, Ricardo; Ardila-Rey, Jorge Alfredo; Munir, Abu Bakar; Mohd Yasin, Siti Hajar; Bani, Nurul Aini
Highlights: The performance of the RADTIRC was analysed under direct and diffuse radiation. Optical gains of 4.66 under direct and 1.94 under diffuse light were achieved. The experiments show good agreement with the simulations. The RADTIRC is an attractive alternative for BICPV systems. Abstract: Making housing carbon neutral is one of the European Union (EU) targets with the aim to reduce energy consumption and to increase on-site renewable energy generation in the domestic sector. Optical concentrators have a strong potential to minimise the cost of building integrated photovoltaic (BIPV) systems by replacing expensive photovoltaic (PV) material whilst maintaining the same electrical output. In this work, the performance of a recently patented optical concentrator known as the rotationally asymmetrical dielectric totally internally reflective concentrator (RADTIRC) was analysed under direct and diffuse light conditions. The RADTIRC has a geometrical concentration gain of 4.969 and two half acceptance angles of ±40° and ±30° respectively along the two axes. Simulation and experimental work has been carried out to determine the optical concentration gain and the angular response of the concentrator. It was found that the RADTIRC has an optical concentration gain of 4.66 under direct irradiance and 1.94 under diffuse irradiance. The experimental results for the single concentrator showed a reduction in concentration gain of 4.2% when compared with simulation data.